Estonia: A Model for Inter-War Europe?. Issue 1 (1st January 2016) - Smith, David J.
Abstract: While Estonia's 1925 Law on Cultural Self-Government for National Minorities is often cited as a rare functioning example of Renner and Bauer's non-territorial autonomy scheme, there has until recently been comparatively little research on how the law operated in practice. This article analyses the institutions of German and Jewish minority self-government established in inter-war Estonia, arguing that (prior to the eclipse of democracy in 1934, at least) these possessed considerable depth and authoritative competence in the area of cultural and educational policy. Cultural autonomy did not resolve all outstanding points of division between state, majority and (in particular) Baltic German minority; nevertheless, it played a positive role in the regulation of ethnonational tensions. Even less well known is the international resonance of this unique law, which transnational minority activists argued should serve as a general model for the regulation of minority disputes. The League of Nations rightly questioned this claim, and the non-territorial autonomy model was scarcely applied beyond the Baltic region during the 1920s. However, it is still instructive to revisit the 1925 law today, at a time when several post-communist states have adopted minority rights legislation based on similar principles.